Geriatric Oncology (Bangladesh Medical Journal, 2009)
We are growing old. In cancer care, there is no exception. Over one-half of all cancer patients in the United States are over age 60.Elderly represent 12% of the total world population. Over the next 25 years, more than 60% of all cancers diagnosed in people of 55 years old and older in Bangladesh As the number of elderly rise exponentially, we can expect growing numbers of elderly at risk for developing cancer. Without dramatic breakthroughs in cancer prevention and treatment, it will have a major impact on the magnitude of cancer problem. In the meantime, when we are growing old and facing cancer, several important realities need to address. What is most important to consider in treatment planning for cancer, is not what the patient's age is, but rather about the baseline level of function and fitness despite chronologic age. In the absence of co-morbid conditions, advanced age should not be a deterrent to cancer therapy with a curative intent. Without other chronic illness which states impair kidney, liver, lung and heart function, older patients can expect comparable results to therapeutic regimens as their younger counterparts.   Keywords: Geriatric Oncology DOI: 10.3329/bmj.v37i1.3604 Bangladesh Medical Journal 37(1) 2008 21-23